Effect of bio-pesticide (Anredera cordifolia Ten. and Allium cepa L.) and chemical pesticide (deltamethrin® 25 EC) on visiting arthropod diversity in rice agriculture Ketindan, Malang Regency, Indonesia - Fenti Wahyu Lestari; Zulfaidah Penata Gama; Amin Setyo Leksono (Cogent Food & Agriculture, 2025)
This study aimed to assess arthropod diversity and pest induced damage in rice fields. Field surveys were conducted using the visual encounter method on rice agricultural with the application of chemical pesticides, bio-pesticides, and control. Analyses were conducted using the IBM SPSS Statistics and Principal Correspondence Analysis (PCA) Paleontological Statistics (PAST). The results showed that the highest Shannon-Wiener diversity index was found in control (4.03b ± 0.57), bio-pesticide (3.71b ± 0.56), and chemical (3.06a ± 0.26). The highest Taxa Richness was found in control (21.50c ± 2.99), bio-pesticide (19.00b ± 1.70), and chemical (15.10a ± 0.74). The highest Evenness was found in control (0.91b ± 0.09), bio-pesticide (0.87ab ± 0.11), and chemical (0.78a ± 0.06). The highest dominance index was found in chemical (0.16b ± 0.04), bio-pesticide (0.09a ± 0.06), and control (0.08a ± 0.06). The highest Index of Importance species are Oxya hyla, Caryanda spuria, Atractomorpha crenulata, and Monomorium minimum. The highest pest attack intensity was found in control, followed by bio-pesticide and chemical agriculture. All treatments have the highest percentage of orders, namely the Orthoptera and Coleoptera. Meanwhile, the families with the highest percentages are Acrididae and Coccinellidae. The findings may guide appropriate pest management decisions.